Effect of Heat Treatment on Antioxidant and Antimicrobial Activity of Croton gratissimus and Xylopiaaethiopica Spices - أحمد عفراء عوض الله; Adam, Yassir Salah Ibrahim; Hussien, Amna Mokhtar; Hassan, Mohammed Elamin (Journal of agricultural, environmental and veterinary sciences, 2020)
Background and objective Croton gratissimus and Xylopiaaethiopicaare tropical African shrubs or small tree with corky bark. It is traditionally used as a febrifuge, styptic, cathartic and is medic for dropsy. This study was designed to determine antioxidant, antimicrobial and toxicity of local spices Crotongratissimus (A), Xylopiaaethiopica (B) and measure effect of heat process on their characteristics of antioxidant, antimicrobial activity, and toxicity. Materials and methods Samples were purchased from JubelAulia and Klakla Al Lafa Markets, Sudan and prepared samples for analysis in three replicates. All samples were extracted by ethanol (80%) A Crotongratissimus and B Xylopiaaethiopica and extract treated by heat treatment (80°C) C Crotongratissimus and D Xylopiaaethiopica. Antioxidant activity was determined by using (DPPH) detector. Results: There were found the extracts with and without heat treatment (A, B, C and D) were grading from highest to lowest, respectively. Antimicrobial activity of (Croton gratissimus, Xylopiaaethiopica) extracts were determined against Bacillssubtilis, Staphylococcus aureus, Escherichia coli, Pseudomonasaeruginosa, and Candida albicans. Toxicity of extracts (Croton gratissimus, Xylopiaaethiopica) was determined for edible matter by using (MTT) assay method, and there were no toxic in both of them. Conclusion: African spices (Croton gratissimus, Xylopiaaethiopica) exhibited the highest antimicrobial, antioxidant activities without any toxicity even in cooked food products.